Bioefficacy of Teak wood (Tectona grandis L.f.) extracts against Aedes aegypti (L.) and Culex quinquefasciatus Say larvae - ทองขาว คณพศ; ชูแก้ว สกุลทิพย์; ศรีเผือก วันสงกรานต์ (Disease Control Journal, 2014)
The objective of this research was to investigate the efficacy of Teak wood (Tectona grandis L.f.) extracts obtained from both maceration and Soxhlet methods on mortality of the 3rd - 4th instars larvae of Aedes aegypti (L.) and Culex quinquefasciatus Say by using the dipping bioassay test. The mortality rates from different concentrations (0 (control), 0.25, 0.50, 1.00, 2.50 and 5.00% (v/v)) at 24 hours were trailed. The results showed the concentration of 5.00% obtained from maceration extraction was the highest toxic to Ae. aegypti (L.) larvae, causing 98.00% mortality and the mortality rates of the concentrations from 0.00-0.50% were not significantly different (p<0.05). More over, the soxhlet-extracted Teak at a concentration of 5.00% exhibited 100% mortality while the mortality rates of the concentrations from 0.00-0.50% were not significantly different (p<0.05). The mortality of Ae. aegypti larvae from both extraction methods was also not significantly different (p<0.05). For the mortality of Cx. quinquefasciatus Say larvae, the extract at 5.00% gained from maceration showed the highest mortality rates with 77.00% and the mortality rates of the concentrations from 0-0.50% were not significantly different (p<0.05). In addition, the Teak wood extract from soxhlet at a concentration of 5.00% displayed 100% mortality and the mortality rates of the concentrations from 0.00-0.50% were not significantly different (p<0.05). How¬ever, the mortality of Cx. quinquefasciatus larvae from both extraction techniques was statistically signifi¬cant (p<0.05). The Teak wood extract from soxhalation showed a high efficiency on average mortality than the extract from the maceration at 31.67 and 28.00%, respectively. Besides, the interaction between the extraction methods and concentration level was also shown. It was found that Soxhlet-extracted Teak wood at concentrations of 5.00% presented the highest mortality rate (100%). Therefore, the Teak wood extract in this study is likely to be further applied as larvicide for controlling the larval mosquitoes.